Roman Pottery Discovered on the Dacian Site of Răcătău (Bacău County, Romania): The case of Pontic Sigillata - Popescu, Mariana-Cristina (Rei Cretariae Romanae Fautorum Acta, 2015)
The Geto-Dacian site of Răcătău is located on a terrace on the left bank of river Siret, on the spot called “Cetăţuie” (The Fortress), at about the mid distance between the villages of Pănceşti and Răcătău. Archaeological research started there in 1968 and continued almost without interruption until the end of the 1990s; it allowed specialists to identify three distinct areas inside the La Tène site: a higher terrace, fortified during certain periods, generally called “the acropolis”, a civilian settlement, and a tumular necropolis.